Alkaline‐Earth‐Metal‐Ions Blending Enhanced Self‐Activated and Bi3+‐Activated Mechanoluminescence from Ca1‐xBaxZnOS - Jia, Jingna; Gao, Xuwen; Zou, Guizheng (Advanced functional materials, 2022)
The self‐activated mechanoluminescence (ML) of oxysulfides MZnOS (M = Ca, Sr, Ba) is very weak, and bright ML from these hosts is usually achieved with activator‐doping strategy. Herein, a promising alkaline‐earth‐metal‐ion blending strategy, instead of activator doping, is proposed to achieve intense and self‐activated ML from MZnOS. Upon partially substituting the Ca2+ of CaZnOS with Ba2+ and vice versa, intense and eye‐visible ML is achieved via exerting a small mechanical stimulus of 2 N onto the obtained Ca1‐xBaxZnOS (0 < x < 1). The luminescence center for ML of Ca1‐xBaxZnOS is intrinsic oxygen vacancy, so that Ca1‐xBaxZnOS can give off efficient and self‐activated ML. Under optimum conditions, the maximum ML emission of Ca0.84Ba0.16ZnOS is about 50‐folds and 170‐folds to that of CaZnOS and BaZnOS, respectively. Promisingly, Bi3+ can be incorporated into the lattice of Ca1‐xBaxZnOS, transferring ML center from the oxygen defects of Ca1‐xBaxZnOS to the activator of Ca0.96‐xBaxZnOS:Bi0.04, and eventually enable further enhanced ML by about twofolds. This alkaline‐earth‐metal‐ion blending strategy can also enhance Bi3+‐activated ML from M0.96ZnOS:Bi0.04, the maximum emission for ML of Ca0.80Ba0.16ZnOS:Bi0.04 is 36‐folds and 38 folds to that of Ca0.96ZnOS:Bi0.04 and Ba0.96ZnOS:Bi0.04, respectively. This work opens an avenue to develop new ML hosts and luminophores with efficient emission. The alkaline‐earth‐metal‐ion blending strategy between Ca2+ and Ba2+ ions can enable Ca1‐xBaxZnOS with obviously enhanced emission of both self‐activated and Bi3+‐activated mechanoluminescence than CaZnOS and BaZnOS, respectively. This strategy is a promising alternative to the traditional activator doping stratgy, and opens an avenue to design novel ML materials with effcient emission.